IL-33 and IL-3 synergistically induce CD25 expression on human basophils without functional IL-2 signaling: a potential marker of severe COVID-19 - Retnakumar, Sruthi Vijaya; Singh, Suraj Chandrabhan; Chauvin, Camille; Bayry, Jagadeesh (Frontiers in Immunology, 2025)
CD25 (IL-2 receptor alpha chain) is a key component of the high-affinity receptor for the IL-2 cytokine and regulates the proliferation, survival, and differentiation of immune cells. The expression of CD25 has been demonstrated in basophils of patients with allergic diseases such as asthma. Previous studies have shown that IL-3 priming leads to increased CD25 expression in basophils. However, other potential stimuli that can regulate the CD25 expression on basophils and their possible biological consequences remain poorly understood. Here, we demonstrate that the IL-33 cytokine, a critical driver of type 2 immunity and allergic inflammation, significantly upregulates CD25 expression on IL-3-primed human basophils. Despite high levels of CD25 expression and its ability to capture IL-2 cytokine, basophils fail to express CD122 (IL-2 receptor beta chain), resulting in the absence of downstream signal transducer and activator of transcription 5 (STAT5) phosphorylation and lack of IL-2-mediated survival signals. The binding of IL-2 to basophil-derived CD25 appears to be transient since co-culturing with regulatory T cells (Treg cells) demonstrates that IL-2 remains accessible to Treg cells, enhancing their viability. Furthermore, an analysis of publicly available single-cell RNA sequencing data from COVID-19 patients revealed increased gene expressions of CD25 and CD132 but not CD122 in basophils from severe patients, which is associated with higher levels of IL-3 and IL-33, positioning CD25 on basophils as one of the potential biomarkers for severe COVID-19. Our data advance the understanding of basophil biology and highlight the complex regulation of IL-2 receptor components in basophil-driven inflammation.